2017
DOI: 10.1007/s40093-017-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of laccase production and its application in delignification of biomass

Abstract: Purpose Current research focuses on the biological delignification of biomass by microbial laccase which is an environmentally friendly process. Methods Various statistical approaches were designed for optimization of laccase production like Plackett-Burman design as well as response surface methodology (RSM). A laccase mediator system was designed for the delignification of saw dust which was molecularly characterized by high-performance liquid chromatography (HPLC), Fourier transformation infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…FTIR (PerkinElmer, FTIR1760) analysis was carried out to explore the presence of chemical functional groups in biosurfactant according to previous report (Bagewadi et al 2017). The extracted biosurfactant was freeze-dried by 3.0 (− 1) 0.7 (+ 1) 2.0 (− 1) 1.20 1.86 4 5.0 (+ 1) 0.7 (+ 1) 2.0 (− 1) 4.20 4.27 5…”
Section: Ftir Analysismentioning
confidence: 99%
“…FTIR (PerkinElmer, FTIR1760) analysis was carried out to explore the presence of chemical functional groups in biosurfactant according to previous report (Bagewadi et al 2017). The extracted biosurfactant was freeze-dried by 3.0 (− 1) 0.7 (+ 1) 2.0 (− 1) 1.20 1.86 4 5.0 (+ 1) 0.7 (+ 1) 2.0 (− 1) 4.20 4.27 5…”
Section: Ftir Analysismentioning
confidence: 99%
“…Some methods, such as using supplemental micronutrients (Thiribhuvanamala et al2012), adequate fertilizers (Reyes 2000), mixed materials with low C-N ratios (Zakhary et al 1984), better aeration and drainage (Apetorgbor et al 2015), can be potentially used to improve EFB composting techniques. Usage of laccase-producing Trichoderma to breakdown lignin during the substrate fermentation as reported by Bagewadi and Mulla (2017) was also a potential option to apply.…”
Section: Chemical Decomposition Of Efbmentioning
confidence: 99%
“…(Bhavsar et al 2011;Moreira et al 2014), Mucor racemosus (Bogar et al 2003b), and Sporotrichum thermophile (Singh andSatyanarayana 2006b, Maurya et al 2017), Thermomyces lanuginosus (Makolomakwa et al 2017), and Rhizopus oryzae (Arora et al 2017) have been reported to produce phytase. Several filamentous fungi and their enzyme products are used to break down the bond between the polysaccharides (cellulose and hemicellulose) and lignin in wheat straw to improve its digestibility through the process referred to as biological-pretreatment (Sindhu et al 2016, Choudhary et al 2016, Bagewadi et al 2017. Many previous studies have also reported the ability of filamentous fungi to produce various commercial enzymes from wheat straw (Table 1).…”
Section: Introductionmentioning
confidence: 99%